A Novel E-Nose System for the Characterization of Dissolved Gases in Dielectric Oils - Ardila-Rey, Jorge Alfredo; Cerda-Luna, Matias Patricio; Munoz, Carlos Beltran; De Castro, Bruno Albuquerque [UNESP]; Govindarajan, Suganya (Institute of Electrical and Electronics Engineers (IEEE), 2023)
The electricity sector heavily relies on oil-filled electricity equipment, particularly power transformers, which are critical and costly components in power generation and transmission systems. However, concerns arise as many of these assets have surpassed their useful life or are nearing the end of it. For this reason, the monitoring and diagnosis of failures in liquid insulation systems play an important role when it comes to extending the life of these pieces of equipment. In its current state, the measurement systems used to capture and quantify the evolution of gases have limitations hindering their widespread use in routine measurements. These limitations have forced a large part of the research and development efforts to focus on developing and proposing new forms of measurement that can be applied without any type of technical-economic restriction and still provide a much more accurate diagnosis of the failure. This article introduces a novel system that utilizes an electronic nose (E-nose) equipped with eight metal oxide semiconductor (MOS)-type gas sensors to measure dissolved gases in liquid insulation systems. The obtained results validate the system's exceptional performance in differentiating mineral oil samples based on the type and concentration of the predominant gases. This innovative approach shows great promise for routine monitoring and diagnosis, offering an efficient and cost-effective solution. Additionally, it exhibits significant potential for widespread implementation and provides a reliable means of assessing the condition of liquid insulation systems in various electrical assets.
Keywords: Dielectric oils; dissolved gas analysis (DGA); electronic nose (E-nose) system; power transformer